Physicochemical Properties of Oil Mixtures from Virgin Red Palm Oil with Olive Oil, Corn Oil, Soybean Oil or Sunflower Oil - Hasibuan, Hasrul Abdi; Priyanto, Adi (Jurnal Penelitian Kelapa Sawit, 2021)
Virgin red palm oil (VRPO) is an oil contains balanced saturated and unsaturated fatty acids and high bioactive compounds (such as carotene, tocopherol, and tocotrienol). Meanwhile, olive oil (OO), corn oil (CO), soybean oil (SBO), and sunflower oil (SFO) are oils contain high unsaturated fatty acids. Blending two or more types of oil can produce healthy oil with a desired fatty acid profile, oxidative stability, and bioactive compounds. This research was conducted to examine the characteristics of a mixture of VRPO with OO, CO, SBO, or SFO at a weight ratio of 100:0 - 0:100 including free fatty acid, carotene and vitamin E content, fatty acids composition, iodine value, melting point and solid fat content. Increasing the amount of VRPO increased palmitic acid, carotene and vitamin e content, melting point, and solid fat content. Enhancing the amount of OO, CO, SBO or SFO decreased free fatty acid content and increased iodine value. The mixture of VRPO with CO, SBO or SFO produced healthy oils with a ratio of saturated fatty acids: monosaturated fatty acids: polyunsaturated fatty acids close to 1:1.5:1. The mixture of VRPO with OO also produced healthy oil with a ratio of linoleic acid: linolenic acid of 5-10:1. The oil mixtures can be used as cooking oil, baking shortening and margarine that rich bioactive compounds.